1991
DOI: 10.1149/1.2085985
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of Electrochromism of Amorphous  WO 3 ‐ TiO2 Thin Films

Abstract: The degradation of the electrochromism of amorphous WO3 and WO3‐TiO2 films prepared by electron‐beam deposition have been studied. The lifetime of the WO3‐TiO2 films is five times longer than that of the WO3 films. SIMS and XPS analyses have revealed that lithium accumulates as OLi in the WO3 films, but that it cannot accumulate in the WO3‐TiO2 film. O1s electron energy loss spectroscopy (EELS) spectra have indicated that the change of the electronic structure for the WO3‐TiO2 film by coloration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 14 publications
8
79
0
2
Order By: Relevance
“…The Ti was found to promote stability both for crystallization at elevated temperature and for the electrochromic performance under extended cycling in a Li-conducting electrolyte. Our data are consistent with those in prior work [14][15][16][17][18]26,30] as regards crystallization and support earlier evidence concerning the ability of Ti to prevent permanent incorporation of Li. Furthermore, our data indicate that low sputtering powers are connected with improved stability under electrochemical cycling.…”
Section: Remarks and Conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Ti was found to promote stability both for crystallization at elevated temperature and for the electrochromic performance under extended cycling in a Li-conducting electrolyte. Our data are consistent with those in prior work [14][15][16][17][18]26,30] as regards crystallization and support earlier evidence concerning the ability of Ti to prevent permanent incorporation of Li. Furthermore, our data indicate that low sputtering powers are connected with improved stability under electrochemical cycling.…”
Section: Remarks and Conclusionsupporting
confidence: 93%
“…Durability enhancement of EC films of W oxide was investigated in detail many years ago by Matsuoka and Hashimoto [13][14][15] who reported on the effect of the incorporation of numerous metallic additives into evaporated films and found that Ti was beneficial and able to extend the cycling durability in a Li + -conducting electrolyte by a factor of roughly five. Other, supporting studies on the electrochromism in W-Ti oxide have been reported for films prepared by sputtering [16][17][18][19], chemical technology involving spraying [20][21][22] dipping [16,23] or spinning [24][25][26], electrodeposition [27,28] and anodization [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that nanostructured WO 3 , in comparison to their compact bulk forms, offer potential advantages in electrochromic application due to their large surface area that could both increase the contact area between the electrode and electrolyte and reduce the diffusion path of ions through the porous structures [13]. And the electrochromic efficiency of WO 3 can be further improved by doping suitable metal ions with higher electronegativity or lower oxidizing capability than W ions, such as Mo and Ti [14,15]. Recently, one-dimensional (1D) WO 3 nanostructures with large surface areas, including nanowires [16,17], nanorods [18,19] and nanobelts [20], have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed anatase (and even rutile) titania, and in particular tungstenia, niobia and tantalia form intermolecular solid oxide solutions of a high altervalent capacity, compatible both in amorphous and crystalline forms of the edge sharing TiO6 and the corner sharing WO6 octahedrons, with pronouncedly increased electrochromic features even at high contents of the former. [49,50] In fact, highly charged W 6+ cations, like Nb 5+ , additionally favor the spontaneous reversible adsorptive dissociation of water molecules, [12,13] and thereby such electrochromic layers exhibit well defined ion exchange and electron conductive properties. [18−20] Thus, one of the fundamental contributions of the present paper is to show that prevailing anatase titania in the form of a composite mixed valence catalytic hypo-d-(f)-oxide support with tungstenia (and/or even more so niobia, tantalia and molybdenia), behaves in a compatible way and regarding the (Pt/H0.35WO3 ⇔ Pt/W(OH)6) bronze type equilibrium, so that the consequent reversibility features, the same properties as pure tungsten bronze itself, all of them have even further advanced by hypo-f-oxide ingredients (Ce,Gd,Ho,La, etc.)!…”
Section: Striping Voltammetry Evidence For the Primary Oxide Latent Smentioning
confidence: 99%